Ajustes da administração de medicamentos para pacientes idosos com disfagia: Um relato de caso - Mastroianni, Patrícia de Carvalho [UNESP]; Forgerini, Marcela [UNESP] (FapUNIFESP (SciELO), 2018)
An elderly patient, aged 76 years, diagnosed with dysphagia, depression, hypothyroidism, Alzheimer’s disease and mild cognitive deficit, was identified with sertraline and levothyroxine- drug-related problems. Medication Therapy Management (MTM) was used to adjust therapy to the patient’s needs by macerating sertraline tablets and solubilizing them in 10-30 mL of orange juice. The patient was advised to take levothyroxine after fasting. Six months later, pharmaceutical follow-up identified an increase in the Mini-Mental State Exam score from 22 to 26 and a decrease in the Clinical Dementia Rating (CDR) scale score from 1.0 to 0.5 in conjunction with mood and physical improvements, as well as a significant decrease in aggressiveness and agitation. Cognitive deficit may be a result of poor drug administration procedures, leading to drug ineffectiveness. Optimizing levothyroxine and sertraline administration, based on knowledge of their physicochemical properties, improves their clinical effectiveness, including the cognition of patients with Alzheimer’s disease and dysphagia.
Drug administration adjustments for elderly patients with dysphagia: A case report
Keywords: Cognitive dysfunction; Deglutition disorder; Medication errors; Medication therapy management; Pharmaceutical care; Sertraline